2012
DOI: 10.1523/jneurosci.2864-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

NKCC1 Knockdown Decreases Neuron Production through GABAA-Regulated Neural Progenitor Proliferation and Delays Dendrite Development

Abstract: Summary Signaling through GABAA receptors controls neural progenitor cell (NPC) development in vitro and is altered in schizophrenic and autistic individuals. However, the in vivo function of GABAA signaling on neural stem cell proliferation, and ultimately neurogenesis, remains unknown. To examine GABAA function in vivo, we electroporated plasmids encoding short-hairpin RNA against the Na-K-2Cl co-transporter NKCC1 in NPCs of the neonatal subventricular zone (SVZ) in mice to reduce GABAA-induced depolarizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 38 publications
1
64
0
Order By: Relevance
“…We note that previous studies (Jin et al 1999) as well as our data not shown also show that complete lack of GABA signaling (in mutants for the UNC-25 GABA biosynthetic enzyme) are able to rewire the GABAergic DD neurons correctly. In contrast, disruption of Cl 2 gradients in vertebrate nervous systems causes severe developmental defects in the nervous system, not just delays in developmental timing that ultimately result in normal adult structures and normal circuit function (Chudotvorova et al 2005;Akerman and Cline 2006;Ge et al 2006;Cancedda et al 2007;Young et al 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that previous studies (Jin et al 1999) as well as our data not shown also show that complete lack of GABA signaling (in mutants for the UNC-25 GABA biosynthetic enzyme) are able to rewire the GABAergic DD neurons correctly. In contrast, disruption of Cl 2 gradients in vertebrate nervous systems causes severe developmental defects in the nervous system, not just delays in developmental timing that ultimately result in normal adult structures and normal circuit function (Chudotvorova et al 2005;Akerman and Cline 2006;Ge et al 2006;Cancedda et al 2007;Young et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…GABA signaling in the vertebrate brain generally develops prior to glutamate signaling and, if excitatory, potentially provides the initial activity in developing circuits (Saint-Amant and Drapeau 2000; Gao and Van Den Pol 2001;Hennou et al 2002;Gozlan and Ben-Ari 2003;Johnson et al 2003). Genetically manipulating Cl 2 transporters to eliminate early depolarizing effects of GABA leads to defects in dendrite and synapse development (Chudotvorova et al 2005;Akerman and Cline 2006;Ge et al 2006;Cancedda et al 2007;Young et al 2012). However, elucidating the precise linkage between the role of early GABA signaling in specific neurons and a manifested behavior has been difficult due to the complexity of the vertebrate brain.…”
mentioning
confidence: 99%
“…However, GABA can also come from an external source. It was shown that striatal GABAergic neurons located at the border of the V-SVZ could regulate intracellular Ca2+ dynamics in V-SVZ astrocytes through GABA A receptors activation and depolarization of L- and T-type voltage-gated calcium channels (Young et al 2010, Young et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…By facilitating the generation of action potentials, GABA was further found to promote the generation of patterned network activity 3,[11][12][13][14][15] . These data led to the suggestion that GABA, whose synapses assemble before the ones for glutamate 16 , acts as one of the major excitatory neurotransmitters of the developing brain, underlying the activity-dependent growth and differentiation of neurons as well as the assembly of synaptic circuits [17][18][19] . Owing to an increase in membrane conductance, depolarizing GABAergic inputs may modulate neuronal output in a complex and bidirectional manner.…”
mentioning
confidence: 99%